The Transatlantic Las Casas - Roldán-Figueroa, Rady, author.
1 online resource
Keywords: The Transatlantic Las Casas demonstrates the vitality of Lascasian studies. An impressive ensemble of scholars spanning the fields of Latin American studies, philosophy, theology, anthropology, law, literary criticism, and ethnohistory illuminate the complex intellectual web surrounding this controversial figure. This volume offers sophisticated explorations of colonial Latin American and early modern Iberian studies in a single volume from Laura Ammon; Thomas Eggensperger, O.P.; Natsuko Matsumori; Timothy A. McCallister; Luis Mora Rodríguez; David Thomas Orique, O.P.; María Cristina Ríos Espinosa; Rady Roldán-Figueroa; Mario Ruíz Sotelo; Frauke Sachse; Rubén A. Sánchez-Godoy; John F. Schwaller; Garry Sparks; Vanina M. Teglia; Dwight E.R. TenHuisen; Paola Uparela; Ramón Darío Valdivia Giménez; Andrew L. Wilson, and Victor Zorrilla.